Defoliation triggered by climate induced effects in Spanish ICP Forests monitoring plots - de la Cruz, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; Sánchez-salguero, Raúl; Grau, José Manuel; De, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; et al. (Forest Ecology and Management, 2014)
In a context of global change, climate impacts can trigger defoliation processes in different forest species. The ICP Forests network estimates the level of forest defoliation over time in different European countries. Those data are used to related defoliation with potential causal factors. In European Southwestern forests, climate change appears to be the detonating factor of generalized defoliation. The objectives of this study were: (i) identity defoliation trends in forest trees at network of Spanish ICP Forests monitoring plots and, (ii) find out if there are underlying climate factors that trigger defoliation process along the time. The spatiotemporal synchronization of the defoliation response was analyzed with cross-correlation using COFECHA software. The relationship between the 88 climatic variables proposed and defoliation was analyzed using Correlated Component Regression models (CCR models) and Discriminant Analysis (DA). The significance of the variables in each model was compared using contingency tables. A peak of defoliation was observed in the mid-1990s with no recovered to the initial values of the early 1990s. The behavior of the different tree species with respect to defoliation, synchronized both in time and space, involves one or several factors that have a general and similar effect on forests in Spain. The most significant factors related to defoliation were the thermal-related factors, particularly average temperatures in April and June and the thermal oscillation of both the current year and the previous year. Only one drought indicator as statistically significant was identified (A, duration of aridity in months) and suggests that it is of limited relevance in the Spanish forest defoliation conditions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Cross-correlation; crown condition; Forest decline; Mediterranean forests; Synchronization

Dynamics of non-structural carbohydrates in three Mediterranean woody species following long-term experimental drought - Rosas, Teresa; Galiano, Lucia Lucía; Ogaya, Roma Romà; Penuelas, Josep; Martínez-Vilalta, Jordi; Penuelas, Josep; Martínez-Vilalta, Jordi (FRONTIERS IN PLANT SCIENCE, 2013)
Stored non-structural carbohydrates (NSC) have been proposed as a key determinant of drought resistance in plants. However, the evidence for this role is controversial, as it comes mostly from observational, short-term studies. Here, we take advantage of a long-term experimental throughfall reduction to elucidate the response of NSC to increased drought 14 years after the beginning of the treatment in three Mediterranean resprouter trees (Quercus ilex L., Arbutus unedo L. and Phillyrea latifolia L.). In addition, we selected 20 Q. ilex individuals outside the experimental plots to directly assess the relationship between defoliation and NSC at the individual level. We measured the seasonal course of NSC concentrations in leaves, branches and lignotuber in late winter, late spring, summer, and autumn 2012. Total concentrations of NSC were highest in the lignotuber for all species. In the long-term drought experiment we found significant depletion in concentrations of total NSC in treatment plots only in the lignotuber of A. unedo. At the same time, A. unedo was the only species showing a significant reduction in BAI under the drought treatment during the 14 years of the experiment. By contrast, Q. ilex just reduced stem growth only during the first 4 years of treatment and P latifolia remained unaffected over the whole study period. However, we found a clear association between the concentrations of NSC and defoliation in Q. ilex individuals sampled outside the experimental plots, with lower total concentrations of NSC and lower proportion of starch in defoliated individuals. Taken together, our results suggest that stabilizing processes, probably at the stand level, may have been operating in the long-term to mitigate any impact of drought on NSC levels, and highlight the necessity to incorporate long-term experimental studies of plant responses to drought.
The following values have no corresponding Zotero field: pub-location: PO BOX 110, LAUSANNE, 1015, SWITZERLAND publisher: FRONTIERS RESEARCH FOUNDATION accession-num: 24130568
Keywords: crown condition; Drought; Growth; long-term; non-s; non-structural carbohydrates; starch; throughfall; Throughfall manipulation

Dynamics of non-structural carbohydrates in three Mediterranean woody species following long-term experimental drought - Rosas, Teresa; Galiano, Lucia Lucía; Ogaya, Roma Romà; Penuelas, Josep; Martínez-Vilalta, Jordi; Penuelas, Josep; Martínez-Vilalta, Jordi (FRONTIERS IN PLANT SCIENCE, 2013)
Stored non-structural carbohydrates (NSC) have been proposed as a key determinant of drought resistance in plants. However, the evidence for this role is controversial, as it comes mostly from observational, short-term studies. Here, we take advantage of a long-term experimental throughfall reduction to elucidate the response of NSC to increased drought 14 years after the beginning of the treatment in three Mediterranean resprouter trees (Quercus ilex L., Arbutus unedo L. and Phillyrea latifolia L.). In addition, we selected 20 Q. ilex individuals outside the experimental plots to directly assess the relationship between defoliation and NSC at the individual level. We measured the seasonal course of NSC concentrations in leaves, branches and lignotuber in late winter, late spring, summer, and autumn 2012. Total concentrations of NSC were highest in the lignotuber for all species. In the long-term drought experiment we found significant depletion in concentrations of total NSC in treatment plots only in the lignotuber of A. unedo. At the same time, A. unedo was the only species showing a significant reduction in BAI under the drought treatment during the 14 years of the experiment. By contrast, Q. ilex just reduced stem growth only during the first 4 years of treatment and P latifolia remained unaffected over the whole study period. However, we found a clear association between the concentrations of NSC and defoliation in Q. ilex individuals sampled outside the experimental plots, with lower total concentrations of NSC and lower proportion of starch in defoliated individuals. Taken together, our results suggest that stabilizing processes, probably at the stand level, may have been operating in the long-term to mitigate any impact of drought on NSC levels, and highlight the necessity to incorporate long-term experimental studies of plant responses to drought.
Keywords: crown condition; Drought; Growth; long-term; non-s; non-structural carbohydrates; starch; throughfall; Throughfall manipulation

Determinants of drought effects on crown condition and their relationship with depletion of carbon reserves in a Mediterranean holm oak forest - Galiano, Lucía; Martínez-Vilalta, Jordi; Sabaté, Santi; Lloret, Francisco (Tree Physiology, 2012)
Severe droughts may increase physiological stress on long-lived woody vegetation, occasionally leading to rapid defoliation and progressive increase in mortality of overstorey trees. Over the last few years, episodes of drought-induced tree dieback have been documented in a variety of woodlands and forests around the world. However, the factors determining tree survival and subsequent recovery are still poorly understood, especially in resprouter species. We have studied the effects of a single drought episode on crown condition in a holm oak (Quercus ilex L.) forest located in NE Spain 7 years after the drought event. Generalized linear models were used to study the environmental correlates of forest crown condition 7 years after the drought event. Additionally, we evaluated the association between crown condition and the carbon and nutrient reserves stored in lignotubers 7 years after the drought. Our study reveals the multifactor nature of a drought-driven forest dieback in which soil depth and the characteristics of individual trees, particularly their number of stems, determined a complex spatial pattern of tree-level responses. This dieback was associated with a depletion of the carbon reserves in lignotubers 7 years after the episode, representing a reduction of up to 60% in highly drought-damaged trees. Interestingly, in the absence of new acute droughts, successive surveys in 2007–11 showed a direct association between carbon reserves depletion and further deterioration of crown condition. More frequent droughts, as predicted by climate change projections, may lead to a progressive depletion of carbon reserves and to a loss of resilience in Mediterranean resprouter species.
10.1093/treephys/tps02510.1093/treephys/tps025
Keywords: carbon reserves; crown condition; drought resilience; resprouter; tree dieback

Short-term changes of response indicators of ecosystem status in broadleaved forests in Tuscany (central Italy) - Ferretti, M; Bonini, I; Bussotti, F; Celesti, C; Cenni, E; Chiarucci, A; Cozzi, A; De Dominicis, V; Grossoni, P; Leonzio, C (WATER AIR AND SOIL POLLUTION, 1999)
The status of different response indicators of forest condition were measured and assessed between 1995 and 1997 at 6 Permanent Monitoring Plots (PMPs) in Tuscany (central Italy), where beech, holm oak and Turkey oak are the most frequent tree species. Foliage transparency, leaf damage and crown dieback have changed significantly over the monitoring period. Leaf area, length of the current year shoots, and total leaf area changed as well, but only for Turkey oak. Changes were consistent between and within the plots. Different indices of plant diversity showed marked changes, apparently linked to natural dynamics within individual ecosystems. These rapid and contrasting fluctuations in the various indicators of forest ecosystem make it difficult to derive a synthesis about the general condition of ecosystems and - especially - about the effects of air pollution.
Keywords: Biodiversity; crown condition; crown productivity; forest health; long-term monitoring; Permanent plots; response indicators

Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F.; Ferretti, M.; COZZI, A. (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves

Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F; Ferretti, M; Cozzi, A (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves